Customers Satisfaction Toward Service Quality in RFC Restaurant: A Case Study in Kedah - Siti Aminah, Sayuti (2011)
The study investigated the relationship between the five dimension of service quality and the customer satisfaction among customers in four of the Radix Fried Chicken Branch in Kedah, Malaysia. The objective of the study were 1) to examine the level perceived service quality and customers satisfaction, 2) to examine the relationship between service quality and customers satisfaction 3) to determine how the attribute service quality (tangible, reliability, responsiveness, assurance, and empathy) influence and effect customers satisfaction. Based on the literature review a model of relationship was proposed and developed to examine the relationship between the five factors of service quality and customer satisfaction. To test the relationship of the variable in the model, data from 310 customers dining there was taken. To test the relationship hypotheses of the study, correlation, and multiple regression analysis were performed. The correlation analysis suggested positive and significant relationship among five service quality variable and the customer satisfaction. The correlation results suggest that customers satisfaction positively and significantly associate with the perceive level of five service tangibility, reliability, responsiveness, insurance and empathy. The result of the correlation analysis showed that if perceived service quality in all five dimensions is experienced at higher level, customer's satisfaction will be higher. Multiple analysis regression result shows that among the five factors of service quality, empathy, assurance, and the reliability were the three main predictor variable to overall customer's satisfaction and significantly and positively influence overall customer's satisfaction.